2023
DOI: 10.1111/bjop.12674
|View full text |Cite
|
Sign up to set email alerts
|

Effects of relative deprivation on change in displaced aggression and the underlying motivation mechanism: A three‐wave cross‐lagged analysis

Abstract: Displaced aggression refers to pernicious acts against innocent people. To date, little is known about mechanisms underlying dynamic changes in displaced aggression. The present study constructed a cross‐lagged model to examine the dynamic effects of relative deprivation on displaced aggression and the mediation mechanisms underlying these effects. A total of 1130 undergraduate students participated in this three‐wave longitudinal study. The results showed that relative deprivation predicted changes in displac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 107 publications
(150 reference statements)
0
0
0
Order By: Relevance
“…For example, the general aggression model (Anderson & Bushman, 2018;Anderson & Carnagey, 2004) suggests that the distal causal factors of aggression (e.g., deprivation experiences) could affect its proximal causal factors (e.g., moral justification, displacement of responsibility, and dehumanization, which are typical mechanisms of moral disengagement) (Bandura, 2002). Importantly, personal relative deprivation predicts civic moral disengagement after 6 months (Guo et al, 2024).…”
Section: Personal Relative Deprivation and Civic Moral Disengagementmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, the general aggression model (Anderson & Bushman, 2018;Anderson & Carnagey, 2004) suggests that the distal causal factors of aggression (e.g., deprivation experiences) could affect its proximal causal factors (e.g., moral justification, displacement of responsibility, and dehumanization, which are typical mechanisms of moral disengagement) (Bandura, 2002). Importantly, personal relative deprivation predicts civic moral disengagement after 6 months (Guo et al, 2024).…”
Section: Personal Relative Deprivation and Civic Moral Disengagementmentioning
confidence: 99%
“…Additionally, a cross-sectional survey found that the relative deprivation perceived by British adults, compared with lowstatus immigrants (Indian and Polish), was associated with dehumanization (a mechanism of moral disengagement) toward these immigrant groups (Gheorghiu et al, 2022). Second, as a chronic adverse social experience, personal relative deprivation may persist and occur repeatedly (Guo et al, 2024); thus, the deleterious effect of personal relative deprivation could be sustained over a long time. For instance, relative deprivation longitudinally predicts behavioral and mental factors such as aggression (Greitemeyer & Sagioglou, 2019b), life satisfaction, and mental health (Schmitt et al, 2010).…”
Section: Personal Relative Deprivation and Civic Moral Disengagementmentioning
confidence: 99%
See 3 more Smart Citations